Knowledge, Attitude, and Practice of Physiotherapists about Cardiac Rehabilitation Program Adherence among Patients Discharged from the Hospital after Cardiac Surgery in India - Ayman Gondekar; Vijay Pratap Singh; Stephen Rajan Samuel; Harish Raghavan; Bidita Khandelwal; K. Vijaya Kumar (The Scientific World Journal)
Background. In most settings, patients receive phase 1 cardiac rehabilitation in CTVS ICU at the hospital, but there are several barriers to follow-up after patients are discharged from the hospital. Physiotherapists play an important role in the enrolment and continuation of cardiac rehabilitation. Thus, we aim to study the knowledge, attitude, and practice of physiotherapists about CR program adherence among patients discharged from the hospital after cardiac surgery. Objectives. (i) To study the knowledge of physiotherapists about the importance of cardiac rehabilitation after discharge; (ii) to know the attitude of physiotherapists towards cardiac surgery patients after discharge; and (iii) to know what approach various centres are applying for patients after discharge to ensure adherence to cardiac rehabilitation. Methods. A questionnaire was developed with reference to the objectives of the study, which was answered by a total of 127 physiotherapists. Results. The overall response rate was 42.3%; nearly 35.4% of the participants indicated that they knew a lot about CR, while 5.5% said they knew very little. Regarding the program’s content, 36.2% of participants reported having a medium degree of awareness of the diverse CR components, while 8.6% reported having very little knowledge of them. Only about one-third, 35.7% stated that CR in India is effective and 95% believed that CR will have an added value for the country. Approximately 80% of respondents thought that it would be challenging for a physiotherapist to recommend patients to a CR in the nation. Nearly 35% of respondents believed that they, “themselves as physios,” needed to commence CR, and slightly less than 70% thought that doctors were required to choose and refer the patients when asked who should take the initiative to start this kind of programme in the country. A little over 40% of respondents said that insurance firms are also involved in starting a CR programme. Conclusion. Physiotherapists have good knowledge of cardiac rehabilitation. However, their attitude and practice towards adherence to exercise protocols are confounded by various clinician- and patient-level factors.